Trade Openness Effect on Income Inequality: Empirical Evidence from Indonesia - Lestari Agusalim; Fanny Suzuda Pohan (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
This research analyzed the effect of international trade openness to income inequality in Indonesia using Vector Error Correction Model (VECM). The data used is the secondary data, which are the export-import value, gross domestic product (GDP), GDP per capita, open unemployment rate, and Gini index. The results of this study indicate that in the short term the trade openness has negative impact significantly on the income inequality. However, in the long-run, it does not show any significant effect in decreasing the income inequality rate. The impulse response function (IRF) concluded that income inequality gives a positive response, except on the third year. Based on the forecast error variance decomposition (FEDV), the trade openness does not provide any significant contribution in effecting the income inequality in Indonesia, but economic growth does. Nevertheless, in long-term, the economic growth makes the income inequality getting worse than in the short-term.DOI: 10.15408/sjie.v7i1.5527